Global Production A Handbook for Strategy and Implementation - Abele, Eberhard.; Abele, Eberhard.; Meyer, Tobias.; Meyer, Tobias.; Näher, Ulrich.; Näher, Ulrich.; Strube, Gernot.; Strube, Gernot.; Sykes, Richard.; Sykes, Richard. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
What is the best configuration for a global production network? What are the different dynamics in low-cost vs. high-cost countries? Getting the answers right is key to building a competitive and efficient global production network. Centers of economic activity are shifting profoundly, globally and even regionally. Production is shifting even more dramatically than the economy as a whole, making it critical for decision makers to know what criteria matter most and how to make the right decisions on where to invest. Regardless of the industry involved, an optimized global footprint can translate to a competitive advantage. A comprehensive redesign typically yields a 20 to 40 percent reduction in manufacturing costs. Global production and purchasing operations create a platform for entry into new markets. Planning and implementing a sustainable globalization strategy, however, takes considerable effort; this book is there to help in that task. The wealth of experience and analysis featured in Global Production is the result of an extensive survey among leading manufacturing companies as well as countless discussions with executives who have personally wrestled with the issues of "going global." In breadth and depth, the insights it offers surpass what a manager or most individual companies could acquire on their own.